Resiliensi dan Religiusitas Mahasiswa Prodi. Pendidikan Agama Islam Universitas Nahdlatul Ulama’ Sunan Giri Bojonegoro di Masa Pandemi Covid-19 - Silfiyah, Khoirotus; Ni’mah, Roudlotun; Khoiriyah, Siti (Pascasarjana IAIN Kudus, 2022)
Resilience and Religiosity of the Islamic Education Students of the Nahdlatul Ulama Sunan Giri University Bojonegoro during the Covid-19 Pandemic. The coronavirus disease (COVID-19) that emerged at the end of 2019 in Indonesia has had a negative impact on various aspects of human life including in the lives of students, including: the transition of the learning system from offline to online, restrictions on interaction between individuals, changes in rules in the implementation of religious practices and so on. In addition, the quality of students' faith and piety during the COVID-19 pandemic also needs to be maintained through deepening of religious teachings and practice in life, so that efforts to maintain mental health and body resilience are met, and spiritual needs or spirituality in worship and doing good deeds are also fulfilled, so that realize a calm, balanced life without excessive anxiety, fear and worry. This study uses qualitative research methods with analytical descriptive methods, in which the results of this study indicate that the formation of self-resilience in 6th semester PAI study program students is supported by several factors including high self-confidence, a healthy lifestyle, and good social skills and high religiosity is triggered by religious activities such as the implementation of the five daily prayers, the practice of Islamic sunnah such as reading the Qur'an, participating in virtual religious studies and maintaining friendship with religious leaders and the surrounding community. Coronavirus Disease (COVID-19) yang muncul pada penghujung tahun 2019 di Indonesia telah memberikan dampak negatif pada berbagai aspek kehidupan manusia termasuk dalam kehidupan peserta didik.Di antaranya peralihan sistem pembelajaran dari offline ke online, pembatasan interaksi antar individu, perubahan aturan dalam pelaksanaan praktik keagamaan dan sebagainya. Selain itu, kualitas keimanan dan ketakwaan santri di masa pandemi COVID-19 juga perlu dijaga melalui pendalaman ajaran agama dan pengamalan dalam kehidupan, agar upaya menjaga kesehatan jiwa dan ketahanan tubuh terpenuhi, serta kebutuhan spiritual atau spiritualitas dalam beribadah dan beramal juga tercukupi, sehingga terwujud kehidupan yang tenang, seimbang tanpa rasa cemas, takut dan khawatir yang berlebihan. Penelitian ini menggunakan metode penelitian kualitatif dengan metode deskriptif analitis, dimana hasil penelitian ini menunjukkan bahwa terbentuknya kemandirian pada mahasiswa Prodi. PAI semester 6 didukung oleh beberapa faktor antara lain kepercayaan diri yang tinggi, pola hidup yang sehat, dan pola hidup yang baik. keterampilan sosial dan religiusitas yang tinggi dipicu oleh kegiatan keagamaan seperti pelaksanaan sholat lima waktu, praktik sunnah Islam seperti membaca al-Qur'an, mengikuti pengajian virtual dan menjaga silaturahmi dengan tokoh agama dan masyarakat sekitar.